FDI and GDRP in East Java: Analysis for Capital Intensive Industries - Dorothea Bening Larasati (Buletin Ekonomika Pembangunan, 2025)
This study explores the relationship between foreign direct investment (FDI) and regional economic growth in East Java Province, with a specific focus on capital-intensive industries. The topic is crucial as FDI plays an increasingly strategic role in accelerating regional development, particularly in industrialized provinces like East Java. The novelty of this research lies in its focus on one province and the inclusion of all industrial sectors in the analysis, offering a more comprehensive and localized perspective compared to previous studies that typically cover national or multi-provincial scopes. This study contributes to the literature by filling a theoretical gap regarding how sectoral FDI affects regional economic output and offers new empirical insights with direct implications for policy and regional planning. Employing a quantitative research design, the study uses panel data from 2020 to 2024, sourced from the Central Statistics Agency and the Investment Coordinating Board. The analysis was conducted using non-parametric correlation tests and a simple regression model. Findings reveal a positive and significant relationship between FDI and the gross regional domestic product (GRDP), with capital-intensive sectors playing a key role in driving growth. The study concludes that increasing FDI, supported by infrastructure improvements, export expansion, and technological innovation, can significantly enhance sustainable economic growth in East Java. Keywords: Capital Intensive Industries, East Java, FDI, GRDP